Combination of Sacral Neuromodulation and Tolterodine for Treatment of Idiopathic Overactive Bladder in Women: A Clinical Trial - Tang, Hua; Chen, Jian; Wang, Yongfu; Yu, Ting; Guo, Changping; Liao, Xiaoqi (Urology Journal, 2014)
Purpose: To evaluate the efficacy of intermittent percutaneous needle sacral nerve stimulation (IPN-SNS) in women with idiopathic overactive bladder (IOAB) treated with tolterodine. Materials and Methods: A total of 240 female patients diagnosed with IOAB were randomized to receive tolterodine only treatment (group 1, n = 120) or tolterodine combined with IPN-SNS (group 2, n = 120). Each group included 120 participants, who were divided into subgroups depending on whether they had dry OAB (urinary frequency and urgency) or wet OAB (urinary frequency and urgency with urgency incontinence). In the treatment group, patients received percutaneous IPN-SNS plus tolterodine (2 mg once daily), while in the control group, only tolterodine (2 mg once daily) was administered for 3 months. The voiding diary and urodynamic parameters were monitored, and patients’ psychological depression and anxiety scores were recorded before and after treatment. Results: There were significantly greater improvements in the conditions of first desire to void (FDV), maximum cystometric capacity (MCC), and daily average volumes, as well as the daily single maximum voided volumes in group 2 (P = .001) than in group 1. In addition, there were significantly greater decreases in self-rating depression scale (SDS) and self-rating anxiety scale (SAS) scores in group 2 compared with group 1 (P < .001). Conclusion: Combined treatment with tolterodine plus IPN-SNS can not only improve the symptoms of voiding dysfunction but can also reduce the concomitant depression and anxiety in women with IOAB, thereby improving patients’ quality of life.